Implementasi Kebijakan Beasiswa Pemuda Tangguh oleh Dinas Kebudayaan, Kepemudaan dan Olahraga Serta Pariwisata Kota Surabaya - Dwi, Melinda; Isbandono, Prasetyo (Jurnal Inovasi Administrasi Negara Terapan, 2024)
Pemuda Tangguh Scholarship is a policy that aims to help students in Surabaya complete their education. This research analyzes the implementation of the policy by the Department of Culture, Youth and Sports and Tourism the City of Surabaya. It identifies both supporting and inhibiting factors in the policy's implementation. The research uses a descriptive, qualitative approach and applies Grindle's theory with two implementation indicators: content of policy and context of implementation. Content of policy includes interests affected, type of benefits extent of change envisioned, site of decision making, programs implementors, and resources committed. Context of implementation includes power, interests, and strategy of actors involved, institutions and regimes characteristics, as well as compliance and responsiveness. The research shows that the policy is supported by interest in reducing poverty through education, benefits in the form of education costs, and the goal of completing education. The characteristics of the institution also facilitate information exchange between the government and scholarship recipients. However, the policy is hindered by factors such as decision-making, resources, power, interests, and strategies of actors involved, as well as compliance and responsiveness related to the fulfillment of scholarship recipient students. To improve implementation, the study suggests additional training for supervisors, intensified outreach in additional activities in synergy with other agencies, and strict warnings to students to fulfill their obligations as scholarship recipients.